Toward an Embodied Decolonial Pneumatology: Dishoming Space: Oleh Toar Banua Hutagalung - Sinaga, Andri Vincent (Indonesian Journal of Theology, 2024)
A book review of Toward an Embodied Decolonial Pneumatology: Dishoming Space.